EXPLORING PSYCHOSOCIAL BARRIERS AND ECONOMIC INDEPENDENCE AMONG PEOPLE WITH MOBILITY DISABILITIES IN DISTRICT SWAT - Muhammad Jamil; Syed Asad Kamal Jan; Ashraf Ali (International Journal of Contemporary Issues in Social Sciences, 2024)
This research explores the various psychosocial obstacles that create barrier for individuals with mobility disabilities in District Swat from achieving economic independence. Disabilities significantly impact daily life, presenting unique hurdles in terms of finding employment and achieving financial self-sufficiency. The study aims to understand how psychosocial factors impact economic independence and to explore how individuals in this group deal with these challenges. The study’s objectives include identifying the psychosocial barriers that limited economic independence. This study evaluating how these barriers affect job opportunities and financial well-being, and exploring the coping strategies and resilience of the individuals involved. By reviewing existing literature, this research place itself within the broader field of disability studies, providing insights into societal attitudes, workplace adjustments, and the emotional aspects of disability in the employment context. In terms of methodology, the study will use a purposeful sampling approach to select participants from the District Swat community with mobility disabilities. Data will be collected through interview guide, and group discussions, using method. Thematic analysis will be employed to interpret the data. Expected outcomes include a comprehensive understanding of the psychological and social barriers faced by individuals with mobility disabilities in their pursuit of economic independence. The study will focus on particular challenges related to employment and finance, examining how individuals in this group manage them. The significance of this study lies in its potential to inform policymakers, advocacy groups, and service providers about the unique challenges faced by individuals with mobility disabilities in District Swat. By uncovering the psychosocial aspects of economic independence, the research aims to contribute to the development of practical interventions and support systems that promote inclusivity and empower individuals navigating mobility disabilities to achieve economic self-sufficiency. In conclusion, this research aims to shine a light on the psychosocial complexities of economic independence for individuals with mobility disabilities in District Swat. Through its findings, it hopes to foster a more inclusive society, ensuring that economic opportunities are within reach for everyone, regardless of physical abilities.